Re-examining the value proposition for Competency-Based Medical Education - Dagnone, Jeffrey Damon; Bandiera, Glen; Harris, Kenneth (Canadian Medical Education Journal, 2021)
The adoption of competency-based medical education (CBME) by Canadian postgraduate training programs has created a storm of excitement and controversy. Implementing the system-wide Competency by Design (CBD) project initiated by the Royal College of Physicians & Surgeons of Canada (RCPSC), is an ambitious transformative change challenge. Not surprisingly, tensions have arisen across the country around the theoretical underpinnings of CBME and the practicalities of implementation, resulting in calls for evidence justifying its value. Assumptions have been made on both sides of the argument contributing to an atmosphere of unhealthy protection of the status quo, premature conclusions of CBME’s worth, and an oversimplification of risks and costs to participants. We feel that a renewed effort to find a shared vision of medical education and the true value proposition of CBME is required to recreate a growth-oriented mindset. Also, the aspirational assertion of a direct link between CBME and improved patient outcomes requires deferral until further implementation and study has occurred. However, we perceive more concrete and immediate value of CBME arises from the societal contract physicians have, the connection to maintaining self-regulation, and the potential customization of training for learners.